Development of STEAM Learning Module to Improve Students' Science Process Skills in Primary School - Dewi, Naomi Dias Laksita; Agustiningsih, Agustiningsih; Arif, Moh Badrus Sholeh (JIPVA (Jurnal Pendidikan IPA Veteran); Vol 7 No 2 (2023): JIPVA (Jurnal Pendidikan IPA Veteran), 2023)
The learning modules used are still limited to answering questions, there are not many that connect students' knowledge with more meaningful learning, close to problems that are often encountered every day. This research aims to produce valid STEAM learning modules in elementary schools. Validation was carried out by two lecturers and three teachers where they validated the format and graphics, content and language. The research results showed that the format and graphics aspect got 14.8 with a percentage of 92.5%, the content aspect got 17.8 with a percentage of 92% and the language aspect got 14 with a percentage of 90%. In addition, with the results of the student's readability test, a score of 90.7% was obtained. Therefore, STEAM learning modules are suitable for use in elementary schools because they have good validity and increases science process skill.